Post-translational modification of Interferon Regulatory Factor 1 (IRF1) - Khalaf, Ahmed Hassanein Abdelmaksoud (2016)
Interferon Regulatory Factor 1 (IRF1) was the first characterised member of the Interferon Regulatory Factor (IRF) family of transcription factors as an IFNβ activator during viral infection. IRF1 acts as a tumour suppressor protein through the induction of apoptosis and cell cycle arrest. IRF1 is exposed to several post-translational modifications that regulate its function. Ubiquitin modifies IRF1 post-translationally, where ubiquitin G76 ligates to IRF1 lysine amino acids, followed by the building of the polyubiquitin chain. The specific type of polyubiquitination depends on the coactivator that binds to the IRF1 transactivation domain (TAD). Subsequently, ubiquitin targets the IRF1 protein to a distinct molecular pathway mediated by the key molecular mechanism of each polyubiquitination. The ubiquitination requires an enzymatic cascade to form a chain on the surface of the protein substrate. IRF1 is also modified by the attachment of the Small ubiquitin-like modifier (SUMO). For instance, IRF1 SUMOylation suppresses the activity and stabilises IRF1 expression level, compared with IRF1 polyubiquitination, which mainly targets IRF1 for proteasome degradation. However, IRF1 domains and its lysines-modified by ubiquitin are still ambiguous. As such, to understand how the ubiquitin regulates IRF1 protein, this study aimed to identify precise lysine residues in IRF1 that are modified by different polyubiquitination types and determine the impact of this modification on IRF1 stability and transcriptional activity. We, therefore, focused on the IRF1 C-terminal lysine amino acids that carry the possibilities to be ubiquitin acceptors or modified by the SUMO1 variant. It was found that ubiquitin targeted the IRF1 C-terminal domain, mainly K240 was found to be the main acceptor for the IRF1 K48-polyubiquitination. IRF1 transcriptional activity was reduced as a consequence of IRF1 C-terminal K-R substitution within its TAD. C-terminal substitutions K233R, K255R, K276R, or K300R, altered the stability of IRF1 in this pilot study. Finally, the E3 FBXW7α ligase enzyme was found to enhance K48-polyubiquitination and K63-polyubiquitination of IRF1.